Experimental study on the application of a compressed-sensing (CS)-based deblurring method in x-ray nondestructive testing and its image performance. (October 2015) - Cho, H.M.; Cho, H.S.; Kim, K.S.; Lim, H.W.; Park, S.Y.; Lee, S.R.; Kim, K.C.; Je, U.K.; Park, Y.O.; Hong, D.K.; Park, C.K.; Woo, T.H.; et al.
Abstract: We investigated the compressed-sensing (CS)-based deblurring framework incorporated with the total-variation (TV) regularization penalty for effective image deblurring of high accuracy in x-ray imaging. We implemented the proposed algorithm and performed a systematic experiment to demonstrate its viability for image deblurring in x-ray nondestructive testing. We obtained x-ray images of several selected electronic components at an x-ray tube condition of 80 kVp and 1.25 mAs and investigated the imaging characteristics in terms of the noise power spectrum and the modulation. We expect the proposed deblurring method to be applicable to improve the image characteristics considerably in x-ray nondestructive testing. Highlights: The compressed-sensing (CS)-based deblurring framework is analyzed. The image characteristics of the recovered x-ray images are significantly improved. It is evaluated for the imaging characteristics in terms of the normalized noise power spectrum (NNPS) and the modulation. The proposed deblurring scheme is to be applicable effectively to improve the image characteristics.